Ambiguous report in anatomic pathology; a southwestern Nigeria experience - Ano-Edwarde GH; Ajao IO; Uduagbamen PK; Onabanjo BD (Ibom Medical Journal)
Background: Ambiguity in anatomic pathology reports is common, with terms like “suspicious for,” “indefinite for,” and “see text” used to express diagnostic uncertainty.